Hannah Arendt on Educational Thinking and Practice in Dark Times: Education for a World in Crisis, Wayne Veck and Helen M. Gunter, Eds. - Azada-Palacios, Rowena A. (Archīum Ateneo, 2024)
Hannah Arendt on Educational Thinking and Practice in Dark Times: Education for a World in Crisis, Wayne Veck and Helen M. Gunter, Eds.